Occupational Risk Factors of Sleep Disorders among Resident Physicians in Al-Azhar University Hospitals in Cairo "Descriptive Analytical Cross-Sectional Study" - Ayman Mahmoud; Ahmed Abd El-Aziz (International Journal of Medical Arts, 2023)
Background: Sleep disorders and fatigue have significant effects on patient safety in various ways as physicians and nurses are always in need of a good vigilance level, sound judgment, and quick response and reaction time, especially in emergency situations. Attention, memory, or coordination level decrease may affect performance and lead to adverse events.Aim of the work: To find out the proportion of daytime sleepiness in resident physicians and to identify the risk factors of developing sleep disorders among them at Al-Azhar university hospitals for men in Cairo.Subjects and Methods: The study included 391 resident physicians at Al-Houssine and Sayed Galal hospitals where the examined resident physicians were classified into two groups: Juniors’ group: defined as resident physicians who are working up to two years and seniors’ group: defined as resident physicians who are working more than two years. A descriptive analytical cross-sectional study was conducted.Results: According to the Epworth sleepiness scale, 82.31% of junior resident and 17.53 % of senior resident physicians have a sleep disorder. Seniors were had a sleep disorder less than juniors in departments of anesthesia [22.22%], Orthopedic [37.50%], Gynecology [40.00%], General Surgery [16.67%] and urology [33.33%]. The highest departments of sleep disorders in juniors were anesthesia [96.30%], Gynecology [95.45%], General Surgery [95.00%] and Orthopedic [93.33%], while the lowest departments were Ear, Nose and Throat department [44.44%]. The highest department of sleep disorders in seniors was Cosmetic, Pediatric, Neurosurgery and Neurology as seniors had sleep disorder by percent of 50%.Conclusion: According to the Epworth sleepiness scale, 82.31% of junior resident physicians had a sleep disorder, there were 17.53 % of senior resident physicians had a sleep disorder.